Genetic Predisposition to Higher Blood Pressure Increases Risk of Incident Hypertension and Cardiovascular Diseases in Chinese. Issue 4 (October 2015) - Lu, Xiangfeng; Huang, Jianfeng; Wang, Laiyuan; Chen, Shufeng; Yang, Xueli; Li, Jianxin; Cao, Jie; Chen, Jichun; Li, Ying; Zhao, Liancheng; Li, Hongfan; Liu, Fangcao; et al.
<x xml:space="preserve">Abstract</x> Although multiple genetic markers associated with blood pressure have been identified by genome-wide association studies, their aggregate effect on risk of incident hypertension and cardiovascular disease is uncertain, particularly among East Asian who may have different genetic and environmental exposures from Europeans. We aimed to examine the association between genetic predisposition to higher blood pressure and risk of incident hypertension and cardiovascular disease in 26 262 individuals in 2 Chinese population-based prospective cohorts. A genetic risk score was calculated based on 22 established variants for blood pressure in East Asian. We found the genetic risk score was significantly and independently associated with linear increases in blood pressure and risk of incident hypertension and cardiovascular disease (P range from 4.57×10–3 to 3.10×10–6). In analyses adjusted for traditional risk factors including blood pressure, individuals carrying most blood pressure–related risk alleles (top quintile of genetic score distribution) had 40% (95% confidence interval, 18–66) and 26% (6–45) increased risk for incident hypertension and cardiovascular disease, respectively, when compared with individuals in the bottom quintile. The genetic risk score also significantly improved discrimination for incident hypertension and cardiovascular disease and led to modest improvements in risk reclassification for cardiovascular disease (all the P<0.05). Our data indicate that genetic predisposition to higher blood pressure is an independent risk factor for blood pressure increase and incident hypertension and cardiovascular disease and provides modest incremental information to cardiovascular disease risk prediction. The potential clinical use of this panel of blood pressure–associated polymorphisms remains to be determined.